Partial Replacement of Cement with Ceramic Waste Powder in the Stabilization of Laterite Soils for Interlocking Earth Blocks. - Iteba, Maurice Victor (Kabale University, 2023)
The research project sets out to study the behaviour of an alternative walling material, compressed stabilized earth brick with ceramic waste dust as a partial replacement for cement. This brick eliminates the kiln firing stage in its production, the stage with the highest environmental burden. Not only because of emission of air pollutants, which increase the greenhouse effect, but also because of the consumption of non-renewable resources in the production of the intensive amounts of energy necessary for the process. There has been no research, however, into the behaviour of bricks with cement partially replaced by ceramic waste dust for stabilization. The main input of this research is the possibility of harnessing the pozzolanic properties of ceramic waste powder (dust) in partial replacement of cement. Rather than by adding only cement, stabilization will be achieved by a combination of cement and ceramic waste powder. This chimes in with today's on¬going concern for developing more sustainable construction materials since the ceramic waste powder (dust) is a waste material obtained from ceramic tile manufacturing industries. Experimental work studies on the neat sample compressed earth brick, the cement stabilized earth brick and compressed stabilized earth brick with ceramic waste dust as a partial replacement for cement are performed. These include soil properties test such as grain size sieve analysis required to classify the soil, the Atterberg limit tests required to determine the soil's plasticity and the standard proctor test to determine the Maximum Dry Density and Optimum Moisture Content of the soil according to British standards namely; BS1377-2:1990. Other tests include, a compressive strength test according to British standards as well as a water absorption test on the various mix blends of the bricks. The results of this study showed that the soil consisted of 59% gravel, 28% fines and 13% sand. The chemical composition of major oxide of the ceramic powder were 69.38